The Prevalence and Factors Associated With Antipsychotic Polypharmacy in a Forensic Psychiatric Sample - Farrell, Christian; Brink, Johann (Frontiers in Psychiatry, 2020)
Despite clinical guidelines limiting the use of multiple concomitant antipsychotics to the most exceptional and treatment resistant cases, the prevalence of antipsychotic polypharmacy has been increasing worldwide. There has been minimal research investigating the prevalence of antipsychotic polypharmacy in forensic psychiatric samples and the correlates associated with antipsychotic polypharmacy. This cross-sectional study aimed to establish the prevalence of antipsychotic polypharmacy in a forensic psychiatric inpatient sample and to investigate the demographical, clinical, and forensic factors associated with polypharmacy. All patients (N = 142) were prescribed at least one antipsychotic at the time of the study. Antipsychotic polypharmacy was prescribed to 54.93% of patients. Logistic regression results indicated increased length of hospitalization, high/medium security level, treatment with clozapine, and depot antipsychotic prescription were predictive of being placed on an antipsychotic polypharmacy regimen. The results suggest that those who are prescribed multiple antipsychotics are long stay patients who present with higher clinical complexity. The results from this study can be used to inform clinical practice leaders about the prevalence of antipsychotic polypharmacy in a forensic psychiatric institution. More research is needed to understand the clinical justifications for prescribing multiple antipsychotics in a forensic psychiatric sample and ways to safely reduce the prevalence of antipsychotic polypharmacy.